Modes of action of a small molecule antiviral compound targeting yellow fever virus NS4B protein - Fuxuan Wang; Zhao Gao; Bo Chen; Zhengyuan Jiang; David M. Renner; Jiaqi Li; Gideon Tolufashe; Yanming Du; Ju-Tao Guo; Jinhong Chang (Proceedings of the National Academy of Sciences, 2025)
Yellow fever virus (YFV) replicates its RNA genome in membranous vesicles derived from the invagination of endoplasmic reticulum membranes, designated as replication organelles (ROs). Nonstructural protein 4B (NS4B) of flaviviruses play essential roles in the biogenesis of ROs and evasion of innate immune responses. We report herein that the binding of an antiviral agent, acetic acid benzodiazepine (BDAA), to YFV NS4B not only rapidly inhibits YFV RNA synthesis, but also induces the activation of cytoplasmic double-stranded RNA (dsRNA)-sensing pathways to accelerate the apoptosis of infected cells. Genetic analyses revealed that all the three cytoplasmic dsRNA-sensing pathways contribute to YFV induction of apoptosis, whereas only retinoic acid-inducible gene I-like receptors and RNase L pathways are required for BDAA acceleration of infected cell death. Our findings support the notion that BDAA binding of NS4B impairs the integrity of ROs, leading to the inhibition of viral RNA synthesis and exposure of viral RNA replication intermediates for the activation of dsRNA sensors and acceleration of infected cell apoptosis. The unprecedented modes of action support the ongoing development of a potent BDAA derivative as a therapeutic agent of yellow fever that continues threatening the lives of millions of people.